The Brief Aggression Questionnaire: Reliability, validity, and structure - WEBSTER, G.D, (Institutional Knowledge at Singapore Management University, 2014)
A key problem facing aggression research is how to measure individual differences in aggression accurately and efficiently without sacrificing reliability or validity. Researchers are increasingly demanding brief measures of aggression for use in applied settings, field studies, pretest screening, longitudinal, and daily diary studies. The authors selected the three highest loading items from each of the Aggression Questionnaire's (Buss & Perry, 1992) four subscales--Physical Aggression, Verbal Aggression, anger, and hostility--and developed an efficient 12-item measure of aggression--the Brief Aggression Questionnaire (BAQ). Across five studies (N = 3,996), the BAQ showed theoretically consistent patterns of convergent and discriminant validity with other self-report measures, consistent four-factor structures using factor analyses, adequate recovery of information using item response theory methods, stable test-retest reliability, and convergent validity with behavioral measures of aggression. The authors discuss the reliability, validity, and efficiency of the BAQ, along with its many potential applications